Gone are the days - Cook, Richard J.; Gould, Mark Landre; Hocutt, Richard; Rodan, Nicole; Tucker, Gregory M.; Henriksen, Lance, 1940-; Berenger, Tom, 1950-; Lush, Billy, 1981-; Steedle, Meg; Railsback, Steve, 1948-; Trejo, Danny, 1944-; Shoreline Entertainment (Firm); et al. (Santa Monica, CA : Lions Gate Entertainment, 2018)
With his days winding down, an aging gunman sets out on an epic quest to perform one last good deed, hoping to save his soul.
Title from disc label.
Originally released as a motion picture in 2018.
Special features: "Behind the scenes of Gone are the days" featurette; cast and crew interviews; trailer gallery.
Lance Henriksen, Tom Berenger, Billy Lush, Meg Steedle, Steve Railsback, Danny Trejo.
MPAA rating: R; for violence, language, some drug material and nude images.
DVD, 16x9 widescreen 2.40:1 presentation; 5.1 Dolby digital audio.
Keywords: Redemption -- Drama; Gunfighters -- Drama; Fathers and daughters -- Drama; Western films; Feature films; Fiction films; Video recordings for the hearing impaired; Drama